2012
DOI: 10.1126/scitranslmed.3003393
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A 2A Receptor Activation Prevents Wear Particle–Induced Osteolysis

Abstract: Prosthesis loosening, associated with wear-particle–induced inflammation and osteoclast-mediated bone destruction, is a common cause for joint implant failure, leading to revision surgery. Adenosine A2A receptors (A2AR) mediate potent anti-inflammatory effects in many tissues and prevent osteoclast differentiation. We tested the hypothesis that an A2AR agonist could reduce osteoclast-mediated bone resorption in a murine calvaria model of wear-particle–induced bone resorption. C57Bl/6 and A2A knockout (A2ARKO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 44 publications
4
106
2
Order By: Relevance
“…Here we describe, for the first time, a direct effect of A2AR activation on bone regeneration in vivo, either via direct activation of the receptor or by enhancing extracellular adenosine levels by blockade of Ent1 transporter. Previously, we reported that activation of the A2AR inhibits osteoclast differentiation (17)(18)(19) both in vitro and . Immunohistochemistry for markers of bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we describe, for the first time, a direct effect of A2AR activation on bone regeneration in vivo, either via direct activation of the receptor or by enhancing extracellular adenosine levels by blockade of Ent1 transporter. Previously, we reported that activation of the A2AR inhibits osteoclast differentiation (17)(18)(19) both in vitro and . Immunohistochemistry for markers of bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The adenosine A1R is critical for osteoclast differentiation and function; A1R blockade or deletion suppresses receptor activated by NF-kB ligand (RANKL)-induced NF-kB activation in vitro, increases bone density, and prevents ovariectomy-induced bone loss in vivo (14)(15)(16). Stimulation of the A2AR inhibits M-CSF/RANKL-stimulated osteoclast differentiation and function in vitro, in part by decreasing IL-1b and TNF-a secretion (17), and the selective A2AR agonist CGS21680 reduces wear particleinduced bone pitting and porosity in vivo, increasing cortical bone and bone volume compared with control mice (18). Strong evidence implicates a role for A2BR in osteoblast differentiation and function (19).…”
mentioning
confidence: 99%
“…However, more recent work has suggested that stimulation of the A2A receptor by adenosine or selective agonists can both stimulate (Pellegatti et al, 2011) and inhibit (Mediero et al, 2012b) osteoclast formation. A2A receptor activation has also been shown to prevent the osteolysis that occurs during prosthesis loosening, a common cause of joint implant failure (Mediero et al, 2012a). Pellegatti et al (2011) reported that the A1 receptor was only weakly expressed by osteoclasts and activation of the A1 receptor was recently shown to have no effect on mouse osteoclasts (Pellegatti et al, 2011;He et al, 2012).…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…In terms of the therapeutic role of A2AR receptors, in patients with inflammatory bone disease, A2AR agonists reduce bone pitting and loss by decreasing the number of osteoclasts and the degree of inflammation [61]. A more recent study demonstrated that weekly low-dose methotrexate (MTX) injections decreased bone pitting but treatment with ZM241385, an A2AR antagonist, or knockout of A2AR abrogated this effect.…”
Section: P1 Receptors: A2armentioning
confidence: 99%